Diseño de un sistema de respaldo energético con celdas fotovoltaicas para la reducción de la huella de carbono en la Planta Hidroeléctrica Platanar, San Carlos - Costa Rica - Saborío-Corea, Marvin Fauricio (Instituto Tecnológico de Costa Rica, 2019)
The project was carried out at Central Hidroeléctrica Platanar, built in 1994 and in operation since 1995, which belongs to COOPELESCA R.L. company from 2016 to the present. The company COOPELESCA is committed to the Carbon Neutrality goal, because of this, it has ventured into projects that represent a company's development in renewable energy production in conjunction with environment friendly processes and technologies. In the Central Hidroeléctrica Platanar, it is desired to eliminate CO2 and other pollutants emissions that occur due to the use of the emergency pump, which operates as an energy backup for the machine house building due to disconnections from the national electricity distribution network, and thus, take another step towards the goal of the company. This project proposes to solve this problem from the implementation of a photovoltaic system, which being a renewable energy production technology conforms to the company's wishes. Therefore, the design of a photovoltaic utilization system connected to the network was developed, adapted to the needs of the company. It is proposed that, with the implementation of this project, it will be possible to replace the generator set that produces the pollutant emissions, leaving it as a third resource, and thus obtain the expected environmental benefits, also reducing the energy consumption of the national network, generating economic benefits for the company.
Proyecto de Graduación (Licenciatura en Ingeniería en Electrónica). Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2019.
Keywords: Carbono neutral; Radiación solar; Paneles solares; Sistemas fotovoltaicos; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics